Hinabang ha bag-o nga pamaagi hin panutdu-an lived experiences of Tacloban City Youth Hub Quarantutors - Santillan, Shellah Mae M.; Tuazon, Timmie Gwynette P.
Volunteer tutors from the Tacloban City Youth Hub went through both enriching and challenging experiences as they aspired to create a safe space for the youth and displaced children in the city. The lives of these vulnerable sectors, including the volunteers themselves, were significantly impacted by the COVID-19 pandemic. As such, the researchers asserted that their lived experiences during a global health crisis should be investigated. This paper delved into the volunteering experiences of quarantutors from the Tacloban City Youth Hub during the COVID-19 pandemic. The collection of data was done through in-person interviews with seven quarantutors, and responses were assessed using Clarke & Braun's thematic analysis. Participants reported their struggles regarding tutees' maladaptive behaviors, personal and material limitations, and pandemic-related issues and concerns, to which they responded by using strategic approaches and optimizing the youth hub's tutoring program. They also discussed the beneficial and detrimental implications of volunteer tutoring for them. Volunteering has been a fulfilling pursuit, as they were able to establish meaningful relationships and hone their skills. On the other hand, their volunteering experiences during COVID-19 caused serious setbacks to their mental health. Such experiences suggested the necessity of developing sustainable initiatives to support volunteer tutors in their quest to reduce the effects of poverty on the street children of Tacloban City.